2021
DOI: 10.1002/hsr2.291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidant, malondialdehyde, macro‐mineral, and trace element serum concentrations in Bangladeshi patients with schizophrenia: A case‐control study

Abstract: Background Schizophrenia (SCZ) is an incurable neuropsychiatric disorder generally described by impaired social behavior and altered recognition of reality. For the first time, this study explored serum levels of antioxidants (vitamin A, E, and C), malondialdehyde (MDA), macro‐minerals (calcium, potassium, and sodium), and trace elements (zinc, iron, and selenium) in Bangladeshi patients with SCZ and thereby, discovering any pathophysiological correlation. Methods This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
(110 reference statements)
0
0
0
Order By: Relevance
“…A dosedependent reduction in serum MDA in Wistar rats treated with trona suggests that it may have antioxidant properties. This is because studies have shown that decreasing MDA levels are associated with increasing amounts of antioxidants such as vitamin A, C, and E [39]. Reduced MDA levels can lead to enhanced non-enzymatic antioxidants, reducing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…A dosedependent reduction in serum MDA in Wistar rats treated with trona suggests that it may have antioxidant properties. This is because studies have shown that decreasing MDA levels are associated with increasing amounts of antioxidants such as vitamin A, C, and E [39]. Reduced MDA levels can lead to enhanced non-enzymatic antioxidants, reducing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%